Women with peripartum cardiomyopathy have normal ejection fraction, but abnormal systolic strain, during pregnancy. (4th May 2021) - Tamrat, Ruth; Kang, Yu; Scherrer‐Crosbie, Marielle; Levine, Lisa D.; Arany, Zoltan; Lewey, Jennifer
Abstract: We report a case series of six women with peripartum cardiomyopathy (PPCM) who incidentally underwent echocardiography prior to the clinical presentation of PPCM. For comparison, we identified controls, matched 2:1 on age, race, body mass index, gestational age, and hypertensive disorder. Among the six cases, all were diagnosed with PPCM during the post‐partum period. Pre‐PPCM echocardiograms were performed between 17.7 weeks of gestation and 13 days post‐partum. Baseline left ventricular ejection fraction and size were normal and similar to the 12 matched controls (60% ± 6.6% vs. 61.4% ± 6.3%, P = 0.63) or left ventricular end‐diastolic dimension (4.6 cm ± 0.2 cm vs. 4.5 cm ± 0.4 cm, P = 0.689). There was a trend towards a less negative (more abnormal) mean global longitudinal strain in cases compared with controls (−14% ± 4% vs. −18.3% ± 4.5%, P = 0.0658). Mean global circumferential strain was significantly less negative (more abnormal) in cases compared with controls (−21.5% ± 5% vs. −29.3% ± 7.6%, P = 0.0329). We conclude that women who develop PPCM have normal left ventricular ejection fraction during gestation preceding PPCM, indicating that the disease develops acutely in the peripartum period. Abnormal strain can be detected, however, suggesting that strain imaging could represent a screening method in populations at high risk for PPCM if confirmed in future studies.